Empagliflozin Use and Fournier’s Gangrene: Case Report and Systematic Literature Review - Mario Antunes; Antonio Cabrera de León; Damiano Pizzol; Amir Hussein Abubacar Seni; Mike Trott; Anne Marie Carrie; Petre-Cristian Ilie; Nicola Veronese; Lee Smith (Surgeries, 2021)
Background: Fournier’s gangrene (FG) is a rare necrotising soft tissue infection localised in the genital areas with possible dramatic outcomes. Recently, sodium glucose co-transporter-2 (SGLT2) inhibitors were identified as a risk factor. Methods: We present a case report of a 57-year-old female patient with type 2 diabetes mellitus (T2DM) in treatment with empagliflozin which led to the development of FG. Moreover, we performed a systematic review assessing the association between empagliflozin use and FG. Results: The female patient with 15-years treated diabetes presented a massive FG after 6 months from starting empagliflozin. Over the period of two months, she was successfully treated in a low-income setting. The systematic review included two studies with a total of 9915 participants. Although no participant had FG, there was an increased rate of urinary and genital infection in patients treated with empagliflozin compared to those treated with other antidiabetics or placebo. Conclusions: FG should be considered as a possible complication in patients using SGLT2. Patients should be educated to report early signs of genital infection and healthy behaviours as well as a balanced diet should be promoted to aid in the prevention of FG.